Upholding Human Rights Within The Scope Of International Law Against The Palestinian - Najwa Zultan; Nadia Nur Elkameliati; Muhammad Syahdan Fauzi Abdul Fattah; Farrel Meikaputra Hendrawan; Dedi Mulyadi; Agustian Jatnika Putra (PT Syamilah Literasi Islami, 2024)
The purpose of this study is to analyze the early history of the background of the Israeli and Palestinian conflict that caused human rights violations that occurred during the conflict, especially in the Palestinian territories where many violations of this research were carried out by providing information and analysis of international cooperation to resolve the Israeli and Palestinian conflict through the realm of international law in upholding human rights against the Israeli community Method The approach in this study is to use a normative juridical approach, namely a legal research method that examines library materials or secondary data, thus this research method is also often referred to as doctrinal legal research sourced from secondary data, legal principles, positive legal rules from library materials, laws, and court decisions.